Defining Influencing Success Factors In Global Software Development (GSD) Projects - Anna Yuliarti Khodijah; Andreas Drechsler (IC-ITECHS, 2014)
Context: Global Software Development (GSD) continues to experience substantial growth of trend concerning the development of software virtually distributed throughout different countries. GSD has several advantages as opposed to the collocated development, but there are also a number of challenges. As a project manager, we should know these and find ways to successfully manage the project virtual team. Objective: This paper is to delineate the study to define which factors influence the success of GSD projects. Method: Using the literature review method, 5 GSD success factors-related literature were selected and reviewed to distinguish the relevant success factors as being reported in the literature. Results: The study indicated that there are different opinions in considering which factors are most important to GSD project success. Some experts see the “people” side of the team would contribute most, but others still think that the “geographical” sides (language barriers, culture, distance, time difference) are the most dominant factors. Conclusion: The results obtained in this paper addressed two aspects; one showing that the challenges of GSD is changing, thus making the influencing factors changing too. Second, this paper can serve as a guide and insight for project managers to better understand how to manage and coordinate a virtual talented team across different countries.